2016
DOI: 10.4491/eer.2015.082
|View full text |Cite
|
Sign up to set email alerts
|

Study of different flexible aeration tube diffusers: Characterization and oxygen transfer performance

Abstract: The research aims to study the different flexible rubber tube diffusers used in urban wastewater treatment processes and aquaculture systems. The experiment was conducted in small-scale aeration tank with different physical properties of the tubes that were used as aerators. The volumetric mass transfer coefficient (kLa), oxygen transfer efficiency (OTE) and aeration efficiency (AE) were measured and determined to compare the diffusers. Moreover, the bubble hydrodynamic parameters were analyzed in terms of bub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 9 publications
0
1
0
Order By: Relevance
“…The k L a 20C and AE were used for comparing and evaluating the oxygen transfer performance, as shown in the As shown in Figure 3.8-a, it was found that the values of k L a 20C obtained with the mechanical surface aerator (around 0.3-1.0 1/hr) were greater than those obtained with the LFFA system with stone tube diffuser by about 2 or 3 times (around 0.1-0.3 1/hr). The bubble size and related rising velocity were 3-5 mm and 21-28 cm/s, respectively [2]. According to the results from flexible tube diffuser, it can be noted that similar trend with paddle wheel aerator was observed (0.3-0.8 1/hr).…”
Section: Comparison Of Lffa and Mechanical Surface Aerator In Real Op...supporting
confidence: 61%
See 1 more Smart Citation
“…The k L a 20C and AE were used for comparing and evaluating the oxygen transfer performance, as shown in the As shown in Figure 3.8-a, it was found that the values of k L a 20C obtained with the mechanical surface aerator (around 0.3-1.0 1/hr) were greater than those obtained with the LFFA system with stone tube diffuser by about 2 or 3 times (around 0.1-0.3 1/hr). The bubble size and related rising velocity were 3-5 mm and 21-28 cm/s, respectively [2]. According to the results from flexible tube diffuser, it can be noted that similar trend with paddle wheel aerator was observed (0.3-0.8 1/hr).…”
Section: Comparison Of Lffa and Mechanical Surface Aerator In Real Op...supporting
confidence: 61%
“…However, this result is specific for the flexible rubber tube only, so this topic has to be studied for further about oxygen transfer mechanism through bubble hydrodynamic parameters observation, and enlarge scope into other types of diffuser for several applications [2].…”
Section: Literature Reviewmentioning
confidence: 99%
“…Oxygen concentration can be estimated in a theoretical way as in equation no (1) [6,12] There are many types of aeration systems to supply oxygen to the biological pool as follows:…”
Section: • Aeration Systemmentioning
confidence: 99%